Pengaruh Keterlibatan Kerja Terhadap Kepuasan Kerja Dan Kinerja Pegawai (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya, 2021)
Purpose - This study aims to test and empirically analyze the effect of job involvement on job satisfaction and employee performance Design/methodology/approach - The research method used is quantitative. The sample in this study consisted of 127 employees of representatives of the National Population and Family Planning Agency of Central Kalimantan Province. Determination of the sample using proportional sampling technique. The data analysis process uses the help of SmartPLS 3.3.2 Findings - shows that Job Involvement has a positive and significant effect on job satisfaction and employee performance in the BKKBN of Central Kalimantan Province